Characterization of roseomonas and nocardioides spp. for arsenic transformation - Bagade, Aditi V.; Bachate, Sachin P.; Dholakia, Bhushan B.; Giri, Ashok P.; Kodam, Kisan M. (Journal of Hazardous Materials, 2016)
The metalloid arsenic predominantly exists in the arsenite [As(III)] and arsenate [As(V)]. These two forms are respectively oxidized and reduced by microbial redox processes. This study was designed to bioprospect arsenic tolerating bacteria from Lonar lake and to characterize their arsenic redoxing ability. Screening of sixty-nine bacterial species isolated from Lonar lake led to identification of three arsenic oxidizing and seven arsenic-reducing species. Arsenite oxidizing isolate Roseomonas sp. L-159a being closely related to Roseomonas cervicalis ATCC 49957 oxidized 2 mM As(III) in 60 h. Gene expression of large and small subunits of arsenite oxidase respectively showed 15- and 17-fold higher expression. Another isolate Nocardioides sp. L-37a formed a clade with Nocardioides ghangwensis JC2055, exhibited normal growth with different carbon sources and pH ranges. It reduced 2 mM As(V) in 36 h and showed constitutive expression of arsenate reductase which increased over 4-fold upon As(V) exposure. Genetic markers related to arsenic transformation were identified and characterized from the two isolates. Moderate resistance against the arsenicals was exhibited by the two isolates in the range of 1-5 mM for As(III) and 1-200 mM for As(V). Altogether we provide multiple evidences to indicate that Roseomonas sp. and Nocardioides sp. exhibited arsenic transformation ability. (C) 2016 Elsevier B.V. All rights reserved.

Click chemistry based multicomponent approach in the synthesis of spirochromenocarbazole tethered 1,2,3-triazoles as potential anticancer agents - Chavan, V, Pramod; Desai, V, Uday; Wadgaonkar, Prakash P.; Tapase, Savita R.; Kodam, Kisan M.; Choudhari, Amit; Sarkar, Dhiman (Bioorganic Chemistry, 2019)
A series of spirochromenocarbazole tethered 1,2,3-triazoles were synthesized via click chemistry based one-pot, five component reaction between N-propargyl isatins, malononitrile, 4-hydroxycarbazole, aralkyl halides and sodium azide using cellulose supported CuI nanoparticles (Cell-CuI NPs) as the heterogeneous catalyst. Antiproliferative activity of all the synthesized compounds was investigated against panel of cancer cell lines such as MCF-7, MDA-MB-231, HeLa, PANG-1, A-549, and THP-1. Many of the synthesized compounds exhibited good anti-proliferative activity against breast (MCF-7 and MDA-MB-231) and cervical (HeLa) cancer cells with IC50 values less than 10 mu M. In case of MCF-7 cells, among the nine compounds that showed good anti-proliferative activity, compounds 6f and 6j were found to be highly potent (IC50 , = 2.13 mu M and 4.80 mu M, respectively). In case of MDA-MB-231, three compounds (6k, 6j and 6s) showed antiproliferative activity amongst which 6k was the most potent one (IC50 = 3.78 mu M). On the other hand, in cervical cancer HeLa cells, compounds 6b, 6g, 6s and 6u showed excellent antiproliferative activity (IC50 = 4.05, 3.54, 3.83, 3.35 mu M, respectively). All the compounds were found to be nontoxic to the human umbilical vein endothelial cells (HUVECs). AO and EtBr staining and fluorescence microscopy studies of the active compounds (IC50 < 5 mu M) suggested that these compounds induce cell death by apoptosis.
Keywords: 1; 2; 3-Triazolylspirochromenocarbazole; Anticancer; Apoptotic assay; Click chemistry; Cytotoxicity; heterogeneous catalysis; Multicomponent synthesis